2019
DOI: 10.4274/tpd.galenos.2019.6303
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Secondary Hydatid Cyst: Uterus and Colon Locations in the Same Patient

Abstract: Cystic echinococcosis (CE) is a common helminthic disease induced by the larval form of Echinococcus granulosus (E. granulosus). According to the World Health Organization data, this disease is endemic in South America, Eastern Europe, Russia, the Middle East and China and exhibits a high annual incidence rate of 50 per 100.000 people in these regions (1,2). In humans, the organs that CE is commonly observed are the liver and the lungs. Cysts are identified less frequently in other organs. Cysts may be localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The specificity rate is also reported to be 83% to 88. It has been reported that the combined use of ELISA and IHA tests boosts the overall sensitivity, reaching up to 94.7% [7]. Since the imaging study was also not supporting a diagnosis of hydatid disease, no further serological test was done for our patient.…”
Section: Discussionmentioning
confidence: 86%
“…The specificity rate is also reported to be 83% to 88. It has been reported that the combined use of ELISA and IHA tests boosts the overall sensitivity, reaching up to 94.7% [7]. Since the imaging study was also not supporting a diagnosis of hydatid disease, no further serological test was done for our patient.…”
Section: Discussionmentioning
confidence: 86%
“…There are a few cases of hydatid cyst in adult age group reporting gynecological organ involvement such as ovary, fallopian tube and uterus in the literature (2). The ovaries are the most commonly involved pelvic organ in women and the uterus is the second (3). There is only one reported case of an ovarian hydatid cyst in childhood (4).…”
Section: Introduction Ydatidosis Also Known As Cystic Echinococcosis ...mentioning
confidence: 99%